PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN DETERJEN TOTAL - Puspita Sari, Bella; Isnaini Asiati, Diah (Jurnal Ilmu Manajemen, 2018)
Total detergent is one brand of detergent that is less populous in the eyes of the public. Therefore research aims to determine the effect of the marketing mix on purchasing decisions. Research was developed using associative design. In the study five variables were used, each of which served as the basis for the development of the variables. The sample was chosen by 100 purposively. The primary data needed is collected using a questionnaire. The data is analyzed using multiple linear regression techniques. The test results prove that 1) Simultaneously there is a significant effect of the marketing mix on total detergent purchasing decisions 2) partially the product, price, and distribution have a significant effect on purchasingdecisions. While the distribution has no significant effect on purchasing decisions